2013
DOI: 10.1007/s10577-013-9366-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of a new wheat–rye 4R chromosome translocation line resistant to powdery mildew

Abstract: Rye is an important and valuable gene resource for wheat improvement. However, due to extensive growing of cultivars with disease resistance genes from short arm of rye chromosome 1R and coevolution of pathogen virulence and host resistance, these cultivars successively lost resistance to pathogens. Identification and deployment of new resistance gene sources in rye are, therefore, of especial importance and urgency. A new wheat-rye line, designated as WR41-1, was produced through distant hybridization and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 42 publications
0
51
0
1
Order By: Relevance
“…elongatum to wheat by homoeologous recombination. A wheat streak mosaic virus resistance gene Wsm1 was transferred to wheat from Thinopyrum intermedium (Graybosch et al 2009;Mutti et al 2011;Liang et al 1979) and has been characterized cytogenetically (Ali 2012). The genomic constitution of the leaf rust-resistant wheat-Thinopyrum ponticum partial amphiploid BE-1 has been characterized using FISH and genomic in situ hybridization (GISH) (Sepsi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…elongatum to wheat by homoeologous recombination. A wheat streak mosaic virus resistance gene Wsm1 was transferred to wheat from Thinopyrum intermedium (Graybosch et al 2009;Mutti et al 2011;Liang et al 1979) and has been characterized cytogenetically (Ali 2012). The genomic constitution of the leaf rust-resistant wheat-Thinopyrum ponticum partial amphiploid BE-1 has been characterized using FISH and genomic in situ hybridization (GISH) (Sepsi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…striiformis Puccinia graminis f. sp. tritici Blumeria graminis ND4BL.4RL + 7AS.4RSGerman white rye; WR41-1 [86] Pm20 6BS.6RLProlific rye; WGRC28 [65]ND5DS-4RS.4RLKustro rye and MK25 triticale [87]ND6RLKustro rye and triticale MK25 [87]ND6RGerman white rye; WR49-1 [88] Schizaphis graminum Diurarphis noxia Rhopalosiphum padi Sitobion avenae Mayetiola destructor H25 4BS.4BL-6RLBalbo rye; 88HF16 wheat [65, 89] Aceria tosichell Heterodera avenae CreR 6DS.6RLT-701 triticale derives [90] Heterodera filipjevi ND(6D) 6R[91] a Gene designations according to McIntosh et al [26] unless: b additional with temporary designation or ND no designation …”
Section: Rye As a Source Of Resistance To Biotic Stresses In Wheatmentioning
confidence: 99%
“…Gallego and Benito (1997) found that Al tolerance is controlled by at least two major dominant and independent loci (Alt1 and Alt3) located on chromosomes 6RS and 4R. Powdery mildew resistance genes were also found on chromosomes 4R and 6R (Heun et al 1990;An et al 2013An et al , 2015.…”
Section: Discussionmentioning
confidence: 98%